Analysis of Inverse Kinematics Techniques for 3D Animation Human Characters Using Autodesk Maya - Ahmad Zaid Rahman; Khoirul Umri, Buyut (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
The research with the title "Analysis of Inverse Kinematics Techniques for 3D Animation Human Characters Using Autodesk Maya" aims to find out how to produce 3D animated movements that are appropriate for natural movements in humans by applying inverse kinematics methods. The motion animation reference used is in the form of Taekwondo selfdefense movement called Twieo Ap Chagi by testing the 3D animation character using inverse kinematics method, and 2 tests are carried out by applying the angle of joint freedom to the joint motion and without applying the angle of joint freedom. Based on the results of the implementation in the making of 3D human motion animation using inverse kinematics methods, setting the degree of freedom degrees only applies to the joints of motion, whereas for dead joints and stiff joints does not require setting the angle of degrees of freedom to look natural. There are several parameters that affect to make 3D animation of human characters having natural motion using the inverse kinematics method is the application of the angle of freedom in the joints which is only done on the legs, because it has a higher percentage of accuracy than those who do not apply the angle of freedom in the joints of 2 %. For the hands it is not recommended to use the inverse kinematics method because it has an average percentage of natural accuracy below 50%, and pay attention to the principles of animation which include timing and spacing, pose to pose, anticipation, follow through and overlapping actions, slow in and slow out, arcs, and secondary action. And motion references in the form of video to get natural results that are supported by rigging characters, both using inverse kinematics and forward kinematics